SOKOL SLETS – THE ESSENCE OF GYMNASTICS IN CZECHOSLOVAKIA, CZECH AND SLOVAK REPUBLIC (CELEBRATING 150 YEARS OF GYMNASTICS) - Anton Gajdoš; Marie Provaznikova; Karel Bednar; Stephen J. Banjak (Science of Gymnastics Journal)
History of Sokol gymnastics started in Praque in 1862. The most important task of Sokol organization was healthy nation, which can be more productive and self defending. For the purpose of mass national exercise the Slets were organized. Since organized the first Slet in 1882 and the last one 2012, Slets lived ups and downs, sometimes were even bigger event than Olympic Games. Slets were very influential events, therefore politics interfered and adopted aims and means of Slets; changing name into Spartakiada. With democratic changes in Europe, Slets got new design and image. Internationaly idea of Slets was adopted by FIG and in 1953 the first Gimnaestrada has been organised. Despite Sokol is not so powerfull as it was, the main idea of national healthy physical exercise lives further.